(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this study was to determine how zig-zag run training affects the dribbling ability of high school students at IMMIM boarding schools. Zig-zag run training is a good example of physical exercise for Football players because it can improve their speed and agility. Their ability to dribble is affected by these improvements. For this study, a quasi-experimental design was used in which a sample of 25 students was divided into two groups. The results showed that with a significant difference between the pre-test and post-test, zig-zag run training had a significant effect on students’ dribbling ability.